Implementation of School-Based Management at SD GMIM KOHA - Gloria Ester Verelin Walewangko; Jeffry Sony Junus Lengkong; Elni Jeini Usoh (International Journal Labs, 2023)
This study aims to explore the implementation of school-based management in GMIM Ko Elementary School. The main focus of this study is the role played by school principals, school committees, and education commissions in managing and improving the quality of education in those schools. This study used a qualitative approach by adopting Miles and Huberman data analysis techniques. The data collection method involved in-depth interviews with principals, school committee members, and education commission members. Direct observation is also conducted to understand the dynamics of interaction between the three parties in the context of decision making and implementation of school-based management programs. The results of the study are expected to provide a clear picture of how principals, school committees and education commissions collaborate to achieve school-based management goals at GMIM Ko Elementary School. The implications of these research findings can be used as a basis for improving school-based management policies and practices in similar schools as well as contributing to the literature on the implementation of school-based management. Based on the results of the study revealed differences in understanding of the concept of School Based Management among school principals, education committees and education commissions. School principals focus more independently on managing resources, while education committees and commissions emphasize comprehensive management. This incomprehension can hinder SBM implementation, so training and modules are needed to improve understanding of concepts. Regarding the role of the principal, it is necessary to improve as educators, supervisors, and managers involving all stackholders. School committees need a greater focus on academic programs, while education committees play an important role as mediators and patrons of school ptograms. Obstacles to SBM implementation involve coordination constraints, lack of effective communication and busy stakeholders. Solutions include improved communication, understanding of roles and a culture of cooperation. The principal's proactive strategy with direct monitoring, limited consultation, efficient communication and quick decision making, plays a vital role in ensuring the effectiveness of SBM. This approach demonstrates pragmatism and flexibility in managing resources to achieve school goals.